Political leadership and collective goods - Frohlich, Norman; Oppenheimer, Joe A.; Young, Oran R. (Princeton legacy library., 1971)
Using the assumptions of rationality and self-interest common to economic analysis, Professors Frohlich, Oppenheimer, and Young develop a profit-making theory of political behavior as it pertains to the supply of collective goods-defense, law and order, clean air, highways.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.